PENGARUH PENGGUNAAN INFLUENCER MARKETING DALAM MENINGKATKAN BRAND AWARENESS PADA BRAND MS GLOW - Maulana Haris Bagaskara; Olivia Barcelona Nasution; Noormalita Primandaru (Jurnal Ekonomi Dan Bisnis, 2025)
This study aims to analyze the influence of influencer marketing on enhancing brand awareness of the MS Glow brand. The research focuses on five key aspects of influencer marketing: credibility, attractiveness, congruence, interaction, and overall promotional effectiveness. A quantitative approach with a survey method was employed, and data were collected through questionnaires distributed to respondents familiar with MS Glow products. The research employed a quantitative approach using Structural Equation Modeling–Partial Least Square (SEM-PLS). Data were collected through questionnaires distributed to 135 respondents familiar with MS Glow products. The findings reveal that all dimensions of influencer marketing play a crucial role in shaping and strengthening brand awareness. Influencer attractiveness and credibility emerged as the most influential factors in building emotional connections and consumer trust toward the brand. Furthermore, the congruence between the influencer’s image and the brand’s values, along with active audience engagement, reinforces positive brand perception. The study concludes that a well-planned and authentic influencer marketing strategy can effectively enhance brand awareness in the highly competitive cosmetics industry.